Phase transformation, thermal behavior, and magnetic study of new (FeSiBP)100-XCuX glassy alloys obtained by melt-spinning in air (2023)
ABSTRACT: In the current work, a new variation of the FeSiBPCu system with good glass forming ability and soft magnetic properties was developed and investigated. The efect of copper addition on the FeSiBP base alloy was studied in the system (Fe0.77Si0.08B0.1P0.05)100-xCux with x=0, 0.25, 0.5, 0.75 and 1.0 at%. Microstructural evolution upon the annealing process was evaluated by XRD and TEM, revealing the formation of α-Fe(Si), Fe2B and Fe3(B,P) crystalline phases. VSM allowed to determine that the combination of chemical composition and microstructure with the best soft magnetic properties after the annealing corresponds with the alloy with 0.75% Cu. In addition, activation energy for glass transition and the frst crystallization event were calculated using the Kissinger method. The research fndings demonstrated that maintaining the relationship between the main elements, it is possible to keep the good glass forming ability with the possibility of developing a nanocrystalline structure with soft magnetic performance.